Selected determinants of the professional identity of dietitian in the contextof legal regulations on the practice of dietitian in Poland and the European Union - Skrzypek, Michał; Pachocka, Lucyna; Goral, Karolina; Partycka-Skrzypek, Adamina (Polish Journal of Public Health, 2018)
The subject of the article is the present status of the profession of dietitian in the Polish healthcare system, taking into account the analysis of the current legislation in force that defines the principles of employment of dietitians and the practice of the dietitian in Poland in the context of relevant provisions of the EU law, with emphasis on the position of dieticians in the health-care systems of selected European Union countries. The study advances the thesis that the current status of the profession of dietitian in Poland reflects its incomplete professionalization manifested in the lack of legal regulations on the principles of its practice that are applied in the case of other medical professions. A consequence of the present, comparatively low status of the profession of dietitian in Poland is, inter alia, the hindered availability of professional clinical dietetics counseling under public health insurance, as well as the practice of the profession as a business activity by individuals whose professional qualifications are not subject to verification by professional regulatory bodies. This produces a risk to patients, arising from the fact that interventions not verified by the EBM paradigm are nevertheless implemented as part of dietary counseling.